Analisis akar permasalahan ketidakhadiran siswa MTs Kota Malang menggunakan Root Cause Analysis “5 why analysis” dan Fishbone diagram - Aulia, Egi Dina (Universitas Negeri Malang, 2024)
Abstract Even though the school has set rules in the discipline as a form of symbolic interaction between school members, many students still choose not to attend. This absence means that students do not physically participate in school activities. Student attendance is considered important for learning achievement and enjoyment of school. This research aims to: 1) Find out the factors that influence student absenteeism at MTs Malang City, 2) Describe efforts to increase student attendance at Madrasah Tsanawiyah (MTs) Malang City. This research uses a qualitative approach and descriptive method, where the researcher acts as the main instrument. The research location is MTs Malang City. Data was collected through document studies, field observations and in-depth interviews, as well as literature observations to complete the data. The research results show that student absences at MTs Malang City are influenced by internal, external and social factors. Internal factors include self-awareness, learning concentration, and the ability to follow the learning process. External factors include the school environment, principal, teachers, and school rules. Social factors include the family and community environment. School efforts to increase student attendance include: 1) Consistent implementation of rules, 2) Involving students in activities that encourage discipline, such as scouts, 3) Formulating rules of conduct by involving the homeroom teacher, students and parents. Abstrak Meskipun sekolah telah menetapkan aturan dalam tata tertib sebagai bentuk interaksi simbolik antar warga sekolah, banyak siswa masih memilih untuk tidak hadir. Ketidakhadiran ini berarti siswa tidak berpartisipasi secara fisik dalam kegiatan sekolah. Kehadiran siswa dianggap penting untuk prestasi belajar dan ketertiban sekolah. Penelitian ini bertujuan untuk: 1) Mengetahui faktor-faktor yang mempengaruhi ketidakhadiran siswa di MTs Kota Malang, 2) Mendeskripsikan upaya untuk meningkatkan kehadiran siswa di Madrasah Tsanawiyah (MTs) Kota Malang. Penelitian ini menggunakan pendekatan kualitatif dan metode deskriptif, di mana peneliti berperan sebagai instrumen utama. Lokasi penelitian adalah MTs Kota Malang. Data dikumpulkan melalui studi dokumen, observasi lapangan, dan wawancara mendalam, serta tinjauan literatur untuk melengkapi data. Hasil penelitian menunjukkan bahwa ketidakhadiran siswa di MTs Kota Malang dipengaruhi oleh faktor internal, eksternal, dan sosial. Faktor internal meliputi kesadaran diri, konsentrasi belajar, dan kemampuan mengikuti proses belajar. Faktor eksternal mencakup lingkungan sekolah, kepala sekolah, guru, dan tata tertib sekolah. Faktor sosial meliputi lingkungan keluarga dan masyarakat. Upaya sekolah untuk meningkatkan kehadiran siswa meliputi: 1) Penerapan tata tertib yang konsisten, 2) Mengikutsertakan siswa dalam kegiatan yang mendorong disiplin, seperti pramuka, 3) Merumuskan tata tertib dengan melibatkan wali kelas, siswa, dan orang tua.